Strategi Manajemen Konflik di Tempat Kerja: Dampaknya terhadap Kesejahteraan Karyawan dan Kinerja Organisasi - Ismail, Ismail (Lembaga Yasin AlSys, 2025)
Workplace conflict management is a crucial aspect of fostering employee well-being and improving organizational performance. This article explores common types of workplace conflicts, effective conflict management approaches, the influence of organizational culture on conflict resolution, and its impact on organizational performance. The study employs a literature review method with qualitative analysis of relevant scholarly articles. The findings reveal that task, relationship, and process conflicts affect employee well-being differently, with relationship conflicts having the most detrimental impact. Collaborative approaches, mediation, and open communication are proven effective in enhancing employee well-being and resolving conflicts constructively. Moreover, an inclusive organizational culture plays a key role in the success of conflict management strategies. Effective conflict management contributes to productivity, innovation, and employee retention. This article emphasizes the importance of a holistic approach to conflict management to support organizational sustainability.